Tracking the leavers: towards a better understanding of doctor migration from Ireland to Australia 2008-2018 - Niamh Humphries; John Connell; Joel Negin; James Buchan (BMC, 2019)
Abstract Background The recession of 2008 triggered large-scale emigration from Ireland. Australia emerged as a popular destination for Irish emigrants and for Irish-trained doctors. This paper illustrates the impact that such an external shock can have on the medical workforce and demonstrates how cross-national data sharing can assist the source country to better understand doctor emigration trends. Method This study draws on Australian immigration, registration and census data to highlight doctor migration flows from Ireland to Australia, 2008-2018. Findings General population migration from Ireland to Australia increased following the 2008 recession, peaked between 2011 and 2013 before returning to pre-2008 levels by 2014, in line with the general economic recovery in Ireland. Doctor emigration from Ireland to Australia did not follow the same pattern, but rather increased in 2008 and increased year on year since 2014. In 2018, 326 Irish doctors obtained working visas for Australia. That doctor migration is out of sync with general economic conditions in Ireland and with wider migration patterns indicates that it is influenced by factors other than evolving economic conditions in Ireland, perhaps factors relating to the health system. Discussion Doctor emigration from Ireland to Australia has not decreased in line with improved economic conditions in Ireland, indicating that other factors are driving and sustaining doctor emigration. This paper considers some of these factors. Largescale doctor emigration has significant implications for the Irish health system; representing a brain drain of talent, generating a need for replacement migration and a high dependence on internationally trained doctors. This paper illustrates how source countries, such as Ireland, can use destination country data to inform an evidence-based policy response to doctor emigration.